Liraglutide, a Glucagon-like Peptide-1 Receptor Agonist, Attenuates Development of Cardiac Allograft Vasculopathy in a Murine Heart Transplant Model. Issue 3 (March 2019) - Wang, ZhiMin; Wang, Mengjun; Hu, Xiaofan; Li, Yakun; Ma, DongXia; Li, ShangLin; Zhao, GuangYuan; Xie, YaNan; Shu, Yanwen; Yang, Jun
Abstract : Background: Advances in immunosuppressive therapy have significantly improved short-term but not long-term survival of cardiac transplant recipients; this is largely due to severe cardiac allograft vasculopathy (CAV). Glucagon-like peptide-1 receptor (GLP-1R)-based therapy exerts physiological effects on the cardiovascular system in addition to its traditional role in controlling glucose. We have investigated the effects of liraglutide, a GLP-1R agonist, on the development of CAV in a murine heart transplant model. Methods: Heterotopic murine cardiac transplantation was performed with a major histocompatibility complex class II-mismatched model. Recipient mice were subcutaneously administered vehicle (0.9% saline solution) or liraglutide (300 μg·kg −1 every 12 hours) from the day of transplantation. Allografts were harvested at 2 or 8 weeks and histologically analyzed. Inflammatory infiltrates were measured by immunohistochemistry, and immunofluorescence and western blotting analyzes were used to evaluate GLP-1R expression and markers of endothelial-to-mesenchymal transition (EndMT) in cardiac allografts and human coronary artery endothelial cells challenged with transforming growth factor-beta 1. Results: Glucagon-like peptide-1 receptor was predominantly localized to vascular endothelial cells and was upregulated in cardiac allografts after liraglutide treatment. Liraglutide ameliorated CAV and cardiac fibrosis with reduced inflammatory cell infiltration and downregulated expression of adhesion molecules. Liraglutide inhibited EndMT in allografts and attenuated EndMT by inhibiting Smad3 activation in transforming growth factor-beta 1–treated human coronary artery endothelial cells. Conclusions: Administration of liraglutide from the time of transplantation upregulated GLP-1R in the transplanted heart and reduced cardiac fibrosis, inflammation, and CAV development. Therefore, liraglutide may be a novel therapy for CAV. Abstract : Supplemental Digital Content is available in the text.